Signature of charged to neutral Higgs boson decay at the LHC in SUSY models - Drees, M.; Guchait, M.; Roy, D. P. (Elsevier B.V., 1999)
We study the signature of H+/- decay into h(0)W at the LHC in SUSY models. It has only marginal viability in the MSSM. But in the singlet extensions like the NMSSM one can have a spectacular signature for H+/- decay into (h(0), A(0))W over a significant domain of parameter space. (C) 1999 Published by Elsevier B.V. B.V. All rights reserved.